Human capital development and parental investment in India - Orazio P. Attanasio; Costas Meghir; Emily Nix (Yale University, Economic Growth Center, 2017)
We estimate production functions for cognition and health for children aged 1-12 in India, where over 70 million children aged 0-5 are at risk of developmental deficits. The inputs into the production functions include parental background, prior child cognition and health, and child investments. We use income and local prices to control for the endogeneity of investments. We find that cognition is sensitive to investments throughout the age range we consider, while health is mainly affected by early investments. We also find that inputs are complementary, and crucially that health is very important in determining cognition. Our paper contributes in understanding how investments and early health outcomes are important in child development.
Keywords: 330